The Impact of IFRS on Annual Report Length - Maria Morunga; Michael E. Bradbury (Australasian Accounting, Business and Finance Journal, 2013)
The move to the NZ IFRS has been surrounded by complaints of too much information being provided. This is not simply a matter of the cost of providing the information, but the possibility of data overload. Data overload is an important issue as it impacts information search strategies and decision outcomes. This is relevant for assessing whether the NZ IFRS has achieved its goals of reducing the cost of financial analysis. This paper develops a model of information processing capacity and then examines the impact of the move to international financial reporting by New Zealand listed entities on the quantity of data provided in their annual reports. Our analysis shows that the annual report length increased for 92% of our sample firms. The average increase in size was 29% above the prior years’ annual report and arose through notes to the accounts and accounting policies. Even after transitional information (e.g. accounting policies and reconciliations) the increase was 15%.
Keywords: IFRS adoption; Disclosures; Information overload